(untitled) (XXI Century. Spanish Literature and Culture, 2013)
Creative writing depends on certain characteristics, the most important being the way the writer sees the world and employs his/her talent to interpret and trascend the world around him/her. To this end, intuition is a writer´s indispensable tool: a vehicle to the subconcious, to the world of fantasy, to the uncanny and to the serendipity of the transitional spaces in which he/she lives. The short story writer makes use of memory in conjunction with the imagination, sensory perception, and synesthesia; and resorts to stylistic devices like tropes, that resemble the literary techniques of poetry. Brevity, suggestiveness, ellipsis, depth, are all indispensable qualities that contribute to the conciseness of every short story, that in the contemporary often generate a second story, more and more elusive, underlying the former.